Pattern of glomerular diseases in biopsy proven native kidney in Western Nepal
Background and Aims: Kidney biopsy is decisive while evaluating for the diagnosis of glomerular, vascular, tubulointerstitial and genetic diseases. There is paucity of data on prevalence and pattern of various types of kidney diseases in Nepalese population. We describe various types of kidney diseases in patient population undergoing kidney biopsy at our centre. Methods: This is a prospective analysis of all patients, who underwent percutaneous renal biopsy at Manipal teaching hospital, over a duration of 30 months, i.e. August 2017 to January 2019. All kinds of kidney disease patients were included for kidney biopsy, irrespective of their clinical syndromes and underlying diagnosis. Results: A total of 175 consecutive biopsies were analyzed. The mean age of the patient was 35